2009
DOI: 10.1029/2008gl035997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfuric acid and ammonium sulfate coatings on the ice nucleation properties of kaolinite particles

Abstract: [1] The onset conditions for ice nucleation on H 2 SO 4 coated, (NH 4 ) 2 SO 4 coated, and uncoated kaolinite particles at temperatures ranging from 233 to 246 K were studied. We define the onset conditions as the relative humidity and temperature at which the first ice nucleation event was observed. Uncoated particles were excellent ice nuclei; the onset relative humidity with respect to ice (RH i ) was below 110% at all temperatures studied, consistent with previous measurements. H 2 SO 4 coatings, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
141
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(153 citation statements)
references
References 31 publications
12
141
0
Order By: Relevance
“…The borosilicate glass cover slip was coated with a hydrophobic organosilane. This substrate had a contact angle of 100 • and ensured the surface did not interfere with ice nucleation (Dymarska et al, 2006;Knopf and Lopez, 2009;Koop et al, 1998;Eastwood et al, 2009;. The same procedure was used to examine homogeneous nucleation and the resulting nucleation rates were in good agreement with literature data, thus confirming that the surface did not initiate crystallisation .…”
Section: Methodssupporting
confidence: 67%
“…The borosilicate glass cover slip was coated with a hydrophobic organosilane. This substrate had a contact angle of 100 • and ensured the surface did not interfere with ice nucleation (Dymarska et al, 2006;Knopf and Lopez, 2009;Koop et al, 1998;Eastwood et al, 2009;. The same procedure was used to examine homogeneous nucleation and the resulting nucleation rates were in good agreement with literature data, thus confirming that the surface did not initiate crystallisation .…”
Section: Methodssupporting
confidence: 67%
“…From the inorganic mass concentrations measured by the C-ToF-AMS, the ratio of the measured NH 4 to that predicted from the measured inorganic ions (NH 4MEAS :NH 4PRED ) is proximately 0.68 when the site was in the FT, suggesting that the aerosol is slightly acidic (Middlebrook et al, 2012). The extent to which aerosol sulphate is neutralized can be important for heterogeneous chemistry (Fan and Jacob, 1992) and ice cloud nucleation (Abbatt et al, 2006;Eastwood et al, 2009), and can have implications for aerosol radiative forcing (Martin et al, 2004). The organic aerosol mass is made up of 60% of LV-OOA, contributions of SV-OOA and BBOA to the total organic aerosol always remain less than 10 and 20% respectively (Fig.…”
Section: Initial Free Tropospheric Particle and Gas-phase Propertiesmentioning
confidence: 99%
“…In the CNT, the nucleation rate depends on the contact angle between the ice embryo and the IN. The contact angle is derived based on the laboratory experiments of Eastwood et al (2008Eastwood et al ( , 2009 on uncoated (h = 12 o ) and sulphuric acid-coated (h = 27 o ) kaolinite particles. The concentration of ice crystals (N i ) nucleated in a given time step (Dt) is given by:…”
Section: Model Descriptionmentioning
confidence: 99%
“…For instance, Eastwood et al (2009) have shown that the onset relative humidity with respect to ice at which ice nucleation occurs on sulphuric acid-coated kaolinite particles is substantially increased when compared with uncoated kaolinite particles. Ice nucleation on sulphuric acid-coated kaolinite particles is therefore energetically much more difficult.…”
Section: Introductionmentioning
confidence: 99%